The Copenhagen Sarcopenia Study: lean mass, strength, power, and physical function in a Danish cohort aged 20–93 years. Issue 6 (16th August 2019) - Suetta, Charlotte; Haddock, Bryan; Alcazar, Julian; Noerst, Tim; Hansen, Ole M.; Ludvig, Helle; Kamper, Rikke Stefan; Schnohr, Peter; Prescott, Eva; Andersen, Lars L.; Frandsen, Ulrik; Aagaard, Per; et al.
Abstract: Background: Despite no international consensus on the diagnostic criteria for sarcopenia, low lean mass, muscle strength, and physical function are important risk factors for disability, frailty, and mortality in older individuals, as well as in a wide range of patients with muscle loss. Here, we provide a population‐based reference material of total and regional lean body mass, muscle strength/power parameters, and physical function in a healthy cohort of Danish men and women across the lifespan. Methods: Volunteers aged 20–93 years from the Copenhagen City Heart Study were invited to establish a Danish reference material (Copenhagen Sarcopenia Study) on lean mass characteristics [appendicular lean mass (ALM), iDXA, GE Lunar], muscle function [handgrip strength (HGS), Jamar dynamometer and leg extension power (LEP), Nottingham Power Rig], and physical function [30 s sit‐to‐stand test (STS), 10‐m maximal and habitual gait speed (GS)]. Results: A total of 1305 participants [729 women (age: 56.4 ± 18.9 years, height: 1.66 ± 0.01 m, body mass index: 24.6 ± 4.3 kg/m 2 and 576 men, age: 57.0 ± 17.5 years, height: 1.80 ± 0.07 m, body mass index: 26.0 ± 3.9 kg/m 2 ] completed all measurements and were included in the present analysis. Lean mass characteristics (TLM, ALM, and ALM/h 2 ) decreased with increasing age in both men and women ( P < 0.001). Men demonstrated larger absolute and relative total ALM and higher HGS and LEP compared with women at all age intervals ( P < 0.001). HGS and LEP decreased progressively with age in both men and women ( P < 0.01); 30 s STS performance, habitual GS, and maximal GS decreased at an accellerated rate of decline with increasing age in both men and women ( P < 0.001). Habitual GS was reduced in men and women aged ≥70 years, while maximal GS was reduced from the age of ≥60 years compared with young adults ( P < 0.001). Regardless of sex, 30 s STS was reduced from the age of ≥50 years compared with the young reference group ( P < 0.001) Conclusions: While the power‐based measurements (LEP and 30 s STS) started to decline already at age +50 years, less power‐based parameters (GS and HGS) and lean mass characteristics (TLM, ALM, and ALM/h 2 ) remained unaltered until after the age of +70 years. Notably, the cut‐off thresholds derived in the present study differed from earlier reference data, which underlines the importance of obtaining updated and local reference materials.